The Prevalence Of Child Marriage: Comparitive Study Of Indonesia And Other South Asian States - Retnowulandari, Wahyuni; Wangga, Maria Silvya Elisabeth; Notoprayitno, Maya Indrasti; Ahmad, Nadzriah (Universitas Negeri Gorontalo, 2024)
Child marriage is a serious issue that has yet to be addressed by Indonesia. This practice severely affects the rights of the child and also Indonesian society as a whole. From a human rights perspective, child marriage is a form of gender-based violence. The causes of early marriage in Indonesia include pregnancy out of wedlock, which is also supported by westernized social life as well as the influence of the media, low education, economic factors and patriarchal culture. Meanwhile, other South Asian States such as India are influenced by economic violence against Muslim women perpetrated by their husbands. This practice in India has a detrimental impact on Muslim women's access to health services, educational attainment, social mobility, and employment opportunities. Furthermore, Bangladesh is affected by family poverty, while Pakistan is affected by financial shocks and school dropout rates. Although multiple factors causally affect the prevalence of child marriage, Indonesia and other South Asian States have shown that protective laws may help to lower the rates of child marriages and adolescent fertility. This article analyzes Indonesia's legal framework in efforts to protect child marriages and compares it with other South Asian States. The main issue of this paper is that early marriage violates the children's rights and both the Indonesian government and the international community should be obligated to combat early child marriage. The methodology employed by this article is a qualitative method of comparative legal case study, where secondary data such as books, articles, reports, online web sites, and court cases are analyzed. This article concludes that existing evidence shows that Indonesia and other South Asian states still lack in enforcement and monitoring delays to ensure the rights of the child and protect women. Alternative legal protection should be applied in order to ensure that women and children can gain access to higher education and hold their life in their own hands